Preparation of (Ba,Sr)(0.5)Sm0.5Co0.8Fe0.2O3-delta and (Ba,Sr)(0.5)Nd0.5C0.8Fe0.2O3-delta cathodes for IT-SOFCs - Aquino, Flavia M.
The development of electrochemical devices towards clean energy generation has been intensified in the last years. In this context, fuel cells, and especially intermediate temperature solid oxide fuel cells (IT-SOFC) have received much attention. Perovskite-type materials of composition Ba1-xSrxCo1-yFeyO3-delta, doped or not with rare earth ions, have been quite promising because they have good ionic conductivity and operate at relatively low temperatures (500-750 degrees C). In this study, powders of compositions (Ba,Sr)(0.5)Sm0.5Co0.8Fe0.2O3-delta (BSSCF) and (Ba,Sr)(0.5)Nd0.5Co0.8Fe0.2O3-delta (BSNCF) were prepared using commercial gelatin powder as a polymerizing agent for its use as cathode. The as-prepared powders were calcined at 1000 degrees C and characterized by X-ray diffraction and scanning electron microscopy. Screen-printed symmetrical cells were sintered 1150 degrees C and studied by electrochemical impedance spectroscopy in order to assess the cathode kinetics for the oxygen reduction reaction. The results ASR for BSNCF at 650 degrees C and 750 degrees C were 1.318 and 0.208 Omega.cm(2), respectively, and for the BSSCF cathode was obtained 1.02 and 0.157 Omega.cm(2), respectively. Microstructural features, associated to good electrochemical performance, indicate that these perovskite materials are good candidates as intermediate temperature SOFC cathodes.